2021
DOI: 10.1021/acs.orglett.1c02327
|View full text |Cite
|
Sign up to set email alerts
|

Selective C–C Bond Cleavage of Cycloalkanones by NaNO2/HCl

Abstract: A novel selective fragmentation of cycloalkanones by NaNO2/HCl has been established. The C–C bond cleavage reaction proceeds smoothly under mild conditions, selectively affording versatile keto acids or oxime acids. The methodology can streamline the synthesis of valuable chiral molecules and isocoumarins from readily available feedstocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…[ 18 ] Additionally, single‐atom sites can help reduce the energy barriers for reactant adsorption and activation processes during catalytic conditions. [ 19 ] However, most research focused on metals from IA to IIB groups, leaving the gap for metals from IIIA to VA due to the present difficulty. A few studies reported using aluminum (Al) and indium (In) to dope into g‐C 3 N 4 lattices to improve photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Additionally, single‐atom sites can help reduce the energy barriers for reactant adsorption and activation processes during catalytic conditions. [ 19 ] However, most research focused on metals from IA to IIB groups, leaving the gap for metals from IIIA to VA due to the present difficulty. A few studies reported using aluminum (Al) and indium (In) to dope into g‐C 3 N 4 lattices to improve photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to isolate the TEMPO-adduct product and analyze it by 1 H NMR (Figure S14), implying a process of carbon radical formation was involved in this oxidative C-C bond cleavage reaction [69]. Finally, according to previous homogeneous catalyst case reports, enol ester and peroxy alcohol are possible intermediates [12,[14][15][70][71]. In order to examine the possible reaction intermediates, an enol ester 4a and a peroxy alcohol 5a were synthesized (For details, please see the Supporting Information).…”
Section: Resultsmentioning
confidence: 63%
“…This reaction, suitable for various ketone substrates, is catalyzed by an iridium complex combined with an organophosphorus ligand at high temperature [11]. In 2021, Huang et al reported a selective C-C bond cleavage of cycloalkanones using NaNO2 and HCl to produce keto acids or oximes via a nitroso cycloalkanone intermediate [12]. These excellent studies provide inspiration for subsequent research.…”
Section: Introductionmentioning
confidence: 99%
“…5-Oxohexanoic Acid (2l). 64 Method B was applied. Purification by silica gel column chromatography (hexane/ ethyl acetate = 1:1) afforded a colorless oil (57 mg, 0.44 mmol, 88% yield).…”
Section: -Hydroxy-2-hexanone (2i)mentioning
confidence: 99%